(untitled) (Environmental Smoke, 2025)
This eBook describes the course "Tourism Ambassadors for Ocean Conservation," an initiative launched in April 2025 by the João Pessoa Department of Tourism (SETUR-PB, Brasil), the JP Diving Club, InPact (Institute for Research and Action), the Paraíba Tourism Guides Union (SINGTUR-PB), and Espaço Oceano. The main objective was to train guides and sales operators in nautical and diving tourism, combining economic development with coral reef preservation in the face of the challenges of climate change and bleaching, and presenting regenerative tourism as an opportunity. The training was divided into six theoretical and practical modules, led by experts from various institutions, covering everything from the fundamentals of marine ecology to diving experiments in controlled and coastal environments. Documents such as the Maritime Authority’s Regulations for Underwater Activities and Waterway Traffic (Brazilian Navy) were considered. The National Coastal Management Plan (NPM) is a comprehensive guide and sales representative for the Brazilian Navy. Emergency Action Plan for the Naufrágio Queimado Environmental Protection Area Conservation Unit; government structural programs (e.g. PREAMAR); Ocean Culture Pedagogical Kit, in addition to the premises of the Decade of Ocean Science and the Decade of Ecosystem Restoration.